The Song Of Gandang Tambua - Azizi Afwan; Rafiloza Rafiloza; Rosmegawaty Tindaon (Gestus Journal: Penciptaan dan Pengkajian Seni, 2021)
The Song Of Gandang Tambua is a work of sound art inspired by the phenomenon of the traditional art of Gandang Tasa in Pariaman, West Sumatra. The phenomenon of the existence of Gandang Tasa is the main interest of this paper. The author formulates three things that are the reasons why Gandang Tasa still exists today: œdiversity, œcohesiveness, and people's œlove for the art of Gandang Tasa are the three reasons why Gandang Tambua still exists today. With these three backgrounds, the artist was inspired to create a programa music using traditional western music techniques such as Retrograde, Augmentation, Diminusion, Imitation, Repetition, Sequence and Canon. The method of creation is carried out by several work groupings: Concept Development Method (Observation, Interview, Data Collection and Concept Formulation); and Methods of Realizing the Concept (Exploration, Experimentation, and Application). In describing expression, this musical composition is made in the form of three parts, each of which is entitled œRagam, œKompak and œCinta with a mixed ensemble formation.Keywords: Gandang Tambua, Gandang Tasa, Program Music.